Effectiveness of Homeopathy in Four Autism Spectrum Disorder Cases - Gupta, Neeraj; Saxena, R. K.; Juneja and Malhotra, Ritu A. K. (Homœopathic Links, 2013)
Autism spectrum disorder (ASD) is a neural developmental ailment and causes impaired social interaction and communication by restricted and repetitive behaviour in children. It develops due to unknown causative agents. It has an immense impact on parents and society. There is supposedly no permanent cure for the various symptoms of ASD. However, several remedial measures are available to control the various behavioural symptoms of autism disorder. The homeopathic therapeutic system has been found to be very effective in controlling the behavioural and other related abnormal conditions of ASD. This paper presents four cases of autistic children, having undergone regular homeopathic treatment. The results of the clinical study found quite meaningful improvement in autistic and other behavioural symptoms in all four subjects studied. This study suggests that a homeopathic medicinal regimen does produce positive improvement and modification of autistic symptoms, if followed dutifully.
Keywords: Autism Spectrum Disorder; Belladonna; Bufo rana; Calcarea carbonica; Calcarea phosphorica; Hyoscyamus niger; Natrum muriaticum; Phosphorus; Santoninum; Silicea; Sulphur; Tarantula; Thuja occidentalis; Tuberculinum; Veratrum album